Catalytic and photoresponsive BiZ/CuxS heterojunctions with surface vacancies for the treatment of multidrug-resistant clinical biofilm-associated infections. Issue 44 (4th November 2021) - Nain, Amit; Huang, Hao-Hsin; Chevrier, Daniel M.; Tseng, Yu-Ting; Sangili, Arumugam; Lin, Yu-Feng; Huang, Yu-Fen; Chang, Lung; Chang, Fu-Chieh; Huang, Chih-Ching; Tseng, Fan-Gang; Chang, Huan-Tsung
Abstract : Copper/bismuth sulfide heterojunctions boost the catalytic and photoresponsive properties engendered antibacterial activity against clinically isolated multidrug-resistant bacteria and their associated biofilms. Abstract : We report a one-pot facile synthesis of highly photoresponsive bovine serum albumin (BSA) templated bismuth-copper sulfide nanocomposites (BSA-BiZ/Cu x S NCs, where BiZ represents in situ formed Bi2 S3 and bismuth oxysulfides (BOS)). As-formed surface vacancies and BiZ/Cu x S heterojunctions impart superior catalytic, photodynamic and photothermal properties. Upon near-infrared (NIR) irradiation, the BSA-BiZ/Cu x S NCs exhibit broad-spectrum antibacterial activity, not only against standard multidrug-resistant (MDR) bacterial strains but also against clinically isolated MDR bacteria and their associated biofilms. The minimum inhibitory concentration of BSA-BiZ/Cu x S NCs is 14-fold lower than that of BSA-Cu x S NCs because their multiple heterojunctions and vacancies facilitated an amplified phototherapeutic response. As-prepared BSA-BiZ/Cu x S NCs exhibited substantial biofilm inhibition (90%) and eradication (>75%) efficiency under NIR irradiation. Furthermore, MRSA-infected diabetic mice were immensely treated with BSA-BiZ/Cu x S NCs coupled with NIR irradiation by destroying the mature biofilm on the wound site, which accelerated the wound healing process via collagen synthesis and epithelialization. We demonstrate that BSA-BiZ/Cu x S NCs with superior antimicrobial activity and high biocompatibility hold great potential as an effective photosensitive agent for the treatment of biofilm-associated infections.